(untitled) (Homoeopathy for All, 2023)
Cases of hyperlipidaemia have been increasing in recent years. Current urban lifestyle, including food habits, is to be blamed. A compilation of homoeopathic drugs useful in the management of high lipid profile published erstwhile is a good tool for clinical practice1. That article was based on the studies conducted using those herbs in crude or as extract, etc. This article highlights a few such studies which have been conducted using homoeopathic drugs.